(untitled) (Doctor Virtualis, 2024)
The article aims to formulate a first hypothesis relating to the relationships between the different types of law present in the thought of Bonaventura da Bagnoregio; the reconstruction will take place starting from the bottom, starting from the lex politica, to go back, only in the conclusions, to the lex aeterna, in its double function of foundation and order. The article does not aim to be exhaustive, rather it presents itself as the first step of an investigation that requires other and much more significant levels of in-depth analysis.